Mempertahankan Sorga di Delang: Dilema Sawit dan Hutan - John Christianto Simon (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2016)
Abstract The ecological issue has become crucial and urgent problem to be responded the logically and practically. This very issue is inseparable from a challenge in the form of catastrophic convergence: poverty, injustice, and violence. Analysis on the ecological problem brought us to trace back the problem of thought contributed by certain philosophical and thelogical thought. It has given birth to an absolute anthropocentrism which has been consolidated by certain theology and in turn gave birth to an expansive notion by way of the mastery over nature, even over other human fellow. The absolutisation of ratio brought about the birth of capitalism (globalized imperialism), which in turn created man as homo oeconomicus in which its keyword is injustice. In the middle of the impoverishing massive ecological damage, there is a different story that showed a local community's ability in defending the environmental conservation. A small village, Kudangan, in Delang Subdistrict are in agreement "Defending Delang's Forest against Palm Oil Plantation Expansion". Theologically, the Delang's local community see nature (forest) not only as something with economical value, but as a "home" for the Divine. The Divine abide in hills with its leafy trees in Delang's area. Here, a contextual theology taking into account the local religiosity instilment to help us rediscovering our contextual mission, that which taking into account the primal worldview (read: cosmic religion), whose principal value is be friendly toward nature. Abstrak Isu ekologis kini menjadi isu krusial yang perlu disikapi secara teologis dan praktis. Isu ini sendiri tidak terpisah dari tantangan berupa "kesatuan bahaya besar" (catastrophic convergence): kemiskinan, ketidakadilan, dan kekerasan yang merajalela. Persoalan ekologis tidak terpisah dari paradigma filosofis dan teologis tertentu berupa antroposentrisme absolut dan melahirkan gagasan ekspansif melalui penguasaan atas alam bahkan atas manusia lain. Lahir pula globalisasi imperialisme (globalized imperialism) dan "manusia ekonomi" (homo oeconomicus) yang yang dapat menciptakan ketidakadilan. Di tengah masifnya kerusakan ekologi yang memiskinkan itu terdapat cerita yang berbeda tentang kemampuan masyarakat lokal mempertahankan kelestarian alam. Masyarakat Desa Delang bersehati "Mempertahankan Hutan Delang dari Ekspansi Sawit". Dari kacamata teologis, masyarakat Delang memahami bahwa alam (hutan) bukan sekadar benda yang bernilai ekonomis, melainkan "rumah" bagi Yang Ilahi. Yang Ilahi ber-surga di bukit-bukit yang rimbun dengan pepohonan di wilayah Delang. Di sinilah teologi kontekstual mempertimbangkan penghayatan religiositas lokal untuk membantu kita menemukan kembali misi yang kontekstual, yaitu misi yang mempertimbangkan pandangan dunia primal (baca: agama kosmik), yang nilai utamanya bersahabat dengan alam.